Student Learning Perception toward Inbound and Outbound Student Exchange Mobility in Science Education - Ahmad, Nur; Putra, Pramudya Dwi Aristya; Sutarto, Sutarto; Indrawati, Indrawati; Mahardika, I Ketut (FKIP Universitas Lampung, 2022)
Higher Education Institutions (HEIs) become important key factors for producing qualified graduates and supporting creativity and innovation. The Merdeka Belajar Kampus Merdeka (MBKM) program stive to link and match between higher education graduates is not only with the business world and the industrial world but also with rapidly changing future. The research subjects were outbound and inbound student exchange. Qualitative data is used to determine the students perceptions in learning activities at Science Education Study Program. Learning activities by inbound student at UNEJ used as making material in power point slides (ppt) for group presentations, discussing material and analyzing videos. In UNNES, outbound students get project assignments, progress and presentation in virtual meeting. Outbound students to UM are divided into several small groups to prepare papers, power points (ppt slide), video presentations and discussion through Sipejar. Keywords: learning perception, student exchange and student mobility. DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp740-750